Enhancement in the mechanical behaviour of a Schwarz Primitive periodic minimal surface lattice structure design - Guo, Xiao; Ding, Junhao; Li, Xinwei; Qu, Shuo; Song, Xu; Fuh, Jerry Ying Hsi; Lu, Wen Feng; Zhai, Wei (International journal of mechanical sciences, 2022)
•An improved Schwarz primitive lattice structure with small openings was proposed.•Compression tests and FE simulations were conducted to evaluate their performances.•The compressive strength and energy absorption of new lattices have greatly increased.•A rigid-plastic hardening model was introduced to predict the mechanical response. Triply periodic minimal surface (TPMS) sheet lattice structures are composed of continuous and smooth shells, enabling the achievement of a high surface-to-volume ratio and pore interconnectivity, which represent an emerging solution for lightweight applications. In this study, an improved Schwarz primitive lattice (P-lattice) structure was proposed by redefining the original opening diameter with a shape parameter. Prototypes of different configurations, such as the original P-lattice (OP) structure, modified P-lattice structure with a small opening diameter (SP), and modified P-lattice structure with a big opening diameter (BP) were fabricated via micro-selective laser melting using 316 L stainless steel. Quasi-static compression tests were performed on the fabricated samples. The experimental results indicated that the Young's modulus, compressive strength, and energy absorption of the SP lattice were increased by 25.84%, 15.63%, and 33.02%, respectively, compared with those of the OP structure. A finite element model was established to investigate the mechanical properties and energy absorption of all the designed configurations, and the results showed good agreement with the experimental observations. A rigid–plastic hardening model was also introduced to macroscopically predict the mechanical response and energy absorption of the as-designed lattice structures. The mechanical properties and energy absorption of the SP structure outperformed those of the OP and BP structures. [Display omitted]